2017
DOI: 10.1111/ecc.12686
|View full text |Cite
|
Sign up to set email alerts
|

Effects of preoperative dexamethasone on postoperative pain, nausea, vomiting and respiratory function in women undergoing conservative breast surgery for cancer: Results of a controlled clinical trial

Abstract: The objective was to evaluate whether pre operative administration of dexamethasone improved post operative nausea and vomiting (PONV), pain and respiratory function tests in women undergoing conservative surgery for breast cancer. This was a controlled clinical trial conducted between June 2013 and October 2014. Eighty patients were evaluated. Patients received a pre operative dose of 8 mg of dexamethasone (n = 40) or placebo (n = 40). The data on PONV and pain intensity was obtained and forced spirometry tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 32 publications
0
43
0
Order By: Relevance
“…Six of the included studies used a low dose (4–5 mg) of dexamethasone . Twenty‐six included studies used an intermediate dose of dexamethasone (8–10 mg) . Seven groups studied a high dose of dexamethasone (12–20 mg) .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Six of the included studies used a low dose (4–5 mg) of dexamethasone . Twenty‐six included studies used an intermediate dose of dexamethasone (8–10 mg) . Seven groups studied a high dose of dexamethasone (12–20 mg) .…”
Section: Resultsmentioning
confidence: 99%
“…Two studies were conducted with an open‐label control group, which received a placebo and two studies were conducted in a blinded fashion; however, the control group did not receive a placebo . All other studies were blinded and were conducted with a placebo group . In 20 studies, participants with diabetes were eligible for inclusion in their respective studies .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 13 14 15 ] Dexamethasone 8 mg is effective and safe for the prevention of PONV following different medical and surgical conditions. [ 15 16 17 18 19 ] Multimodal approach to PONV has been advocated in recent guidelines and medical literature[ 11 12 13 ] With a better understanding of pathophysiology of PONV involving different sets of receptors, combination therapy with antiemetics acting through different pathways appear to be the logical choice. A fair number of trials had shown the efficacy of dexamethasone as an antiemetic.…”
Section: Discussionmentioning
confidence: 99%